Factors Associated with Financial Inclusion in Indonesia Before and During COVID-19: Evidence from Global Findex Data - Prasetyoputra, Puguh; Isnasari, Yovita; Prasojo, Ari Purwanto Sarwo; Hermawan, Iwan (Statistics, Optimization & Information Computing, 2025)
This study examines the factors associated with financial inclusion and the use of financial technology (FinTech) in Indonesia, both before and during the COVID-19 pandemic, using the Global Findex data from 2017 and 2021. Multivariable logistic regression models were fitted to analyze the factors associated with formal account ownership, savings, borrowing, mobile/Internet payments, and mobile money services usage. The results suggest that formal account ownership remained stable, whereas savings and borrowing declined during the pandemic. Education was observed as a variable with a significant correlation with financial inclusion and the use of FinTech. Higher income and mobile phone ownership significantly increased the likelihood of inclusion for all the indicators. Female individuals have a higher probability of owning a formal account and saving in one than males. Moreover, the pandemic accelerated the adoption of digital financial services. Policy recommendations include: 1) strengthening financial and digital literacy programs, especially for underserved groups; 2) expanding affordable digital infrastructure; 3) developing gender-responsive financial products; 4) balancing FinTech innovation with consumer protection; and 5) leveraging public-private partnerships to scale digital payment ecosystems. Future research should examine the long-term impacts on household resilience and explore the behavioral factors influencing inclusion beyond socioeconomic variables.